THE EFFECT OF PYROLYSIS TEMPERATURE ON THE HEAT VALUE OF PYRO-OIL USING PLASTIC WASTE - I Made Agus Putrawan (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This work primarily investigated the pyrolysis of smalls scale fixed bed reactor using plastic wastes type LDPE during slow pyrolysis (non-isothermal) in a batch reactor to assess the effect of different temperatures on the product yield and heating value. The calorie bomb of Parr Instrument was performed to investigated heating value of pyro-oil product at different temperatures 250, 275, 300oC. The pyro-oil obtained at higher product yield of 300 oC while the increased temperature will affect to increase the product yield of pyro-oil. The highest heating value of pyro-oil produced at a reactor temperature of 300oC is 9,769.78 cal/gr. From the results of pyro-oil using plastic waste type LDPE, the characteristics of the heating value are equivalent to diesel fuel.